Pati Pregel Pati Singkong Fosfat Sebagai Bahan Pensuspensi Sirup Kering Ampisilin - Anwar, Effionora; SV, Antokalina; Harianto, Harianto (Majalah Ilmu Kefarmasian, 2006)
For most reason for dry suspension is the drug changes from chemical degradation or hydrolysis like ampicillin. The dry syrups that require mixing prior to administration is solving the problem. These suspension are commersial, dry mixtures that require the addition of water at the time of dispensing. Many antibiotics are formulated as dry syrups and are intented for a pediatric patient population. There are usually fewer suspending material in suspension dry syrup than in convensional suspensions. The criteria for selecting inggredients are based both on suitable reconstitution and on physical tipe of powder mixture desired. This research was carried out the possibility of using phycical and chemical modification of cassava starch as suspending material. First, pregelatinized cassava starch was made by heated the cassava starch with added amount water. Secondly, phosphorylated by adding phosphorous oxychloride for making cross-linked reaction and adding sodium monohydrogen phosphate (Na2HPO4) for making substituted reaction respectively. Both of the cassava starch phosphate derived was used in tree formulas dry syrup, as comparative suspending material was Na Alginate. Then dry syrup was evaluated accordance to Indonesian Farmacopea ed IV included sedimentation volume, redispersion, viscosity, flowing properties, pH, and ampicillin content after seven days. The result of evaluation were particle size 355-500 Âµm, flow rate 2,7-4,6 g/ det. Sedimention volume at temperature 27ÂºC during seven days for all formulas were 0,8-1,0, and redispertion 3-5 times. The viskosity of the suspensions were 58,6-357,1 cps .Flowing properties of the liquids were plastis -plastis tixotropic, pH 4,97-5,21, and ampicillin content between 93,12-99,00%.